Endocrine-Disrupting Chemicals: Some Actions of POPs on Female Reproduction. (23rd May 2013) - Gregoraszczuk, Ewa L.; Ptak, Anna
Abstract : Persistent organic pollutants (POPs), such as polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs), polychlorinated biphenyls (PCBs), and polybrominated ethers (PBDEs), chloronaftalens (PCNs), and bisphenol A (BPA), are stable, lipophilic pollutants that affect fertility and cause serious reproductive problems, including ovotoxic action, lack of ovulation, premature ovarian failure (POF), or polycystic ovarian syndrome (PCOS). Most of the representatives of POPs influence the activation of transcription factors, not only activation of aromatic hydrocarbon receptor (AhR), but also the steroid hormone receptors. This minireview will focus on a variety of PAH activities in oocyte, ovary, placenta, and mammary gland. The complexity and diversity of factors belonging to POPs and disorders of the reproductive function of women indicate that the impact of environmental pollution as an important determinant factor in fertility should not be minimize.